Comparison of polyphenols, phenolic acids, and antioxidant activity in sweet potato (Ipomoea batatas L.) tubers after heat treatments - Janette Musilová; Hana Franková; Silvia Fedorková; Judita Lidiková; Alena Vollmannová; Klaudia Sulírová; Július Árvay; Pavel Kasal (Journal of Agriculture and Food Research)
Phenolic compounds (total polyphenol content – TPC, chlorogenic acid – CGA, neochlorogenic acid – neoCGA, cryptochlorogenic acid – cryptoCGA) and the antioxidant activity (AA) by DPPH and FRAP methods were determined in raw peel and flesh of sweet potatoes (white cv. Japanese, orange cv. Beauregard), and in heat-treated flesh (steamed, boiled, microwaved, baked). The TPC in raw orange-fleshed sweet potatoes ranged from 1126 (Croatia – Beauregard) to 3248 (Austria – Beauregard) mg/kg dry weight. Heat treatment significantly increased the CGA and neoCGA content. CryptoCGA in heat-treated samples varied from 5.53 (microwaved Croatia – Japanese) to 119 (steamed Austria – Beauregard) mg/kg dry weight. Higher AA-DPPH was observed in all heat-treated samples, except for microwaved Egypt – Beauregard and Austria – Beauregard, boiled Egypt – Beauregard, and baked Austria – Beauregard samples. The AA-FRAP levels in the Croatia -Japanese, USA – Beauregard, Austria – Beauregard samples increased after all heat treatments. The amount of bioactive compounds and their antioxidant properties in sweet potatoes were both significantly increased by heat treatments.